OBESITY: A BRIEF HISTORICAL REFLECTION OF SOCIAL AND CULTURAL CHANGE IN PROCESS STIGMATIZATION (Fiep Bulletin - online, 2016)
Obesity as a concepthasbecomethrou ghoutthe historyofsociety. At a given time wasassig nedanaestheticvalue, beingsocially accepted. Currently, fromthe perspective ofthehealthobese individual happens to be blamed for theirsituation, beingsocially stigmatized. Thus, the scoring aspects occurred throughout historyt hatled the social and cultural changes are relevant to observe thedevelopment of the construction processo fstigmatizationofobesity. The reflection with respect to the stigmatization of obesity begins in the Middle Ages, historical moment that obesity wasaccepted, butfrownedupon by the church and aristocracy, through the Renaissance where thegreatpaintersportrayedwomen, suggesting a standard offeminine beauty ruledtherounded forms .Butwiththeindustrialization process, recognition of nutrition as animportantareaof ??knowledge, contributions in referentialfashion skinny aesthetic began the process ofstigmatizationofobesity. Especially in Brazilian society there was important momentsthatcontributedto thestigmatizationprocess, such as: rapid rural migration, the establishment of the minimum wage in 1940, intensifiedindustrializationoccurredfrom 1970 ontheentryofwomeninto labor market and the creation of the Real Plan in 1994. itisconcludedthatthe processo fstigmatizationofobesityconstitutes a historical processwith social and cultural transformation sthatinvolve "[...] medicine, science, art , religion, gender, fashion, media, as well as a series of moral andethicalcodes. "(Stenzel 2002, p. 30-31). Finally, thereisan understanding that the process of stigmatization of obesity has intensified sincethesecondhalfofthetwentiethcentury.
Keywords: Obesity. HistoryandSociety. Stigmatization.